TransOdara study: the challenge of integrating methods, settings and procedures during the COVID-19 pandemic in Brazil - Maria Amelia de Sousa Mascena Veras; Thiago Felix Pinheiro; Lenice Galan; Laio Magno; Andréa Fachel Leal; Daniela Riva Knauth; Ana Rita Coimbra Motta-Castro; Rita Suely Bacuri de Queiroz; Philippe Mayaud; Daniel Jason McCartney; Gwenda Hughes; Camila Mattos dos Santos; et al. (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective Sexually transmitted infections (STIs) disproportionately affect transgender women and travestis (TGW), who often lack access to healthcare due to stigma and discrimination. We describe the approach and methodology of a study investigating the prevalence of syphilis, HIV, hepatitis A, B, and C, Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT), and human papillomavirus (HPV) among TGW, as well as their knowledge and perceptions regarding syphilis, to better inform policies to curb STIs among this vulnerable population. Methods: TransOdara was a multicentric, cross-sectional study conducted among TGW in five capital cities from major Brazilian regions between December 2019 and July 2021. Self-identified transgender women and travestis aged >18 years were recruited using respondent-driven sampling after a qualitative formative phase, completed an interviewer-led questionnaire, were offered a physical examination, and were also asked to provide samples from multiple sites to detect various STIs, starting vaccination and treatment when indicated. Results: A total of 1,317 participants were recruited from the five study locations: Campo Grande (n=181, 13.7%), Manaus (n=340, 25.8%), Porto Alegre (n=192, 14.6%), Salvador (n=201, 15.3%), and São Paulo (n=403, 30.6%). The recruitment period varied at each study location due to logistic constraints imposed by the COVID-19 pandemic. Conclusion: Despite the enormous challenges posed by the co-occurrence of the COVID-19 pandemic and field work targeting a vulnerable, elusive, and scattered population, the TransOdara project has been effectively implemented. Caveats did not preclude 1,300 TGW from being interviewed and tested, amid a significant epidemic that disrupted health services and research projects in Brazil and worldwide.